PENERAPAN APLIKASI QUIZIZZ DALAM MENUMBUHKAN MOTIVASI BELAJAR PADA MATA PELAJARAN PAI - Muhammad, Fadhli; Ali, Imron; Ahmad, Fauzi (LPPM Sekolah Tinggi Ilmu Tarbiyah Al Marhalah Al Ulya Bekasi, Indonesia, 2026)
This research aims to analyze the implementation of the Quizizz application in fostering learning motivation in Islamic Religious Education (PAI) for fifth-grade students of SDIT Bina Mulia Mojo. The study uses a qualitative descriptive case study approach with observation, interviews, and documentation as data collection techniques. The findings reveal that the use of Quizizz effectively increases students’ motivation and participation in class. Through the integration of TPACK (Technological Pedagogical Content Knowledge) and Self-Determination Theory, the study demonstrates that Quizizz not only enhances learning outcomes but also strengthens students’ autonomy, competence, and social connectedness. Quizizz is thus considered an effective digital tool for promoting motivation and enthusiasm in Islamic learning.